Subungual Malignant Melanoma: Difficulty in Early Diagnosis - Naveed, Shah; Singh, Gurpreet; Quari, Hasina (Bangladesh Journal of Medical Science, 2013)
A rare case of subungual malignant melanoma in a 43-year-old male, with black dystrophic right thumb nail plate with positive Hutchison sign is presented. Early detection in malignant melanoma is vital for improved treatment outcomes and prognosis. Subungual melanoma presents in a more disguised manner than cutaneous lesions and therefore requires increased vigilance and awareness [1]. Patient underwent disarticulation just distal to the proximal interphalangeal joint. Histopathology confirmed malignant melanoma, and resection free of tumour cells. Our case highlights how any pigmented lesions within the nail bed matrix should raise suspicion and the need for early referral and biopsy. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 322-324 DOI: http://dx.doi.org/10.3329/bjms.v12i3.13200